Toxoplasma-infected subjects report an Obsessive-Compulsive Disorder diagnosis more often and score higher in Obsessive-Compulsive Inventory - Flegr, J; Horáček, J (European psychiatry, 2017)
BACKGROUND: Latent toxoplasmosis, the life-long presence of dormant stages of Toxoplasma in immunoprivileged organs and of anamnestic IgG antibodies in blood, affects about 30% of humans. Infected subjects have an increased incidence of various disorders, including schizophrenia. Several studies, as well as the character of toxoplasmosis-associated disturbance of neurotransmitters, suggest that toxoplasmosis could also play an etiological role in Obsessive-Compulsive Disorder (OCD). METHODS: The aim of the present cross-sectional study performed on a population of 7471 volunteers was to confirm the association between toxoplasmosis and OCD, and toxoplasmosis and psychological symptoms of OCD estimated by the standard Obsessive-Compulsive Inventory-Revised (OCI-R). RESULTS: Incidence of OCD was 2.18% (n=39) in men and 2.28% (n=83) in women. Subjects with toxoplasmosis had about a 2.5 times higher odds of OCD and about a 2.7 times higher odds of learning disabilities. The incidence of 18 other neuropsychiatric disorders did not differ between Toxoplasma-infected and Toxoplasma-free subjects. The infected subjects, even the OCD-free subjects, scored higher on the OCI-R. LIMITATIONS: Examined subjects provided the information about their toxoplasmosis and OCD statuses themselves, which could result in underrating the strength of observed associations. CONCLUSIONS: The results confirmed earlier reports of the association between toxoplasmosis and OCD. They also support recent claims that latent toxoplasmosis is in fact a serious disease with many impacts on quality of life of patients.
Keywords: Obsessive-Compulsive Disorder; toxoplazmóza; Cross-Sectional Studies; Cats; Statistics, Nonparametric; Schizophrenia; Parasites; Middle Aged; mužské pohlaví; průřezové studie; Adult; Risk factors; neparametrická statistika; Learning disabilities; kvalita života; kočky; Infection; Mental disorder; Toxoplasmosis; ženské pohlaví; zvířata; Humans; Toxoplasma; lidé středního věku; schizofrenie; dospělí; Female; Quality of Life; obsedantně kompulzivní porucha; lidé; Male; Animals